ANALISIS EFEKTIVITAS INVENTORY CONTROL INSTALASI FARMASI RUMAH SAKIT AISYIYAH PONOROGO DENGAN METODE ABC VEN - Sawitri, Satwika Budi; Zumaroh, Macfudza Anil; Fitrian, Ahyana; Al Hasanah, Fauziyyah (PC IAI Sragen, 2025)
Drug supplies are important and must be considered so as not to cause losses to hospitals that will have an impact on services to patients. To process and control inventory, ABC VEN analysis is one method that can be used to determine the priority of appropriate drugs based on their cost and therapeutic effects. The purpose of this study was to determine the application of the ABC VEN method in determining the maximum stock at the